(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was conducted to determine the impact of working capital, debt to equity ratio and current ratio on the company’s ability to generate profits. The companies selected are those that are members of the food and beverage sector, where the number of samples selected is 23 companies during 5 research periods. The method used is descriptive verification. The results showed that only der variable had an effect on ROA, while WC and Cr had no effect on ROA.